Using Folklore in Aziz Malaresh’s Novel - Sangar Qader Shekhmohammad Haji (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
Literary geners have a significant impact on each other, sometimes, we as readers can find different geners used in a specific gener, especially a novel. This research entitled “Using Folklore Types in Aziz Mala Resh Novels’’ discusses the probability of using folklore types in novels. The research method is descriptive; those types of folklore focused on, that used in the novel. Also, we get to the conclusion that the novelist used folklore elements extensively.